Self-Reflection of Attitude after Teaching Abroad: A Narrative of Teaching Indonesian to American Students - Dyan Ayu Andawi; Ngadiso Ngadiso; Nur Arifah Drajati (Humaniora, 2019)
This research aimed at exploring how the former participant of teaching abroad reflects intercultural experience in order to know the development of attitude as one of the descriptors of intercultural competence. The attitude being explored were (1) acknowledging the identities of others, (2) respecting otherness, (3) having empathy, (4) identifying positive and negativeemotion, and (5) tolerance for ambiguity. This research applied a qualitative method. The data were taken from the former grantee of Fulbright Foreign Language Teaching Assistant (FLTA) who taught Indonesian to the students of higher education in the U.S in the academic year of 2015/2016. The former grantee was examined after two years of the program. The researchwas based on a narrative inquiry that used an instrument named the Autobiography of Intercultural Encounters. It was a selfreflection portfolio made specifically to reflect an intercultural encounter from the eye of the participant. The results indicate that the participant shows a considerable degree of reflection to five elements of attitude aforementioned. It gives a significant implication that the self-reflection increases the participant awareness upon the experience of otherness thus reinforcing the ability to evaluate the changes in attitude.